Employment and earnings effects of awarding training vouchers in Germany - Annabelle Doerr; Bernd Fitzenberger; Thomas Kruppe; Marie Paul; Anthony Strittmatter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
In 2003, Germany moved from a system in which participants in training programs for the unemployed are assigned by caseworkers to an allocation system using vouchers. Based on the rich administrative data for all vouchers and on actual program participation, we provide inverse probability weighting and ordinary least squares estimates of the employment and earnings effects of a voucher award. Our results imply that after the award, voucher recipients experience long periods of lower labor market success. On average, there are only small positive employment effects and no gains in earnings even four years after the voucher award. However, we do find significantly positive effects both for low-skilled individuals and for degree courses. The strong positive selection effects implied by our estimates are consistent with sizeable cream-skimming effects.
urn:nbn:de:bsz:180-madoc-371057
Keywords: J68; H43; C21; 330; Active Labor Market Policies; Training Vouchers; Treatment Effects Evaluation; Administrative Data